2020
DOI: 10.7717/peerj.8774
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and employment: a cross-sectional study of office workers and unemployed people

Abstract: Background Alcohol is a psychoactive substance with toxic and addictive properties. Biomarkers like GGT, AST, ALT and MCV are influenced by excessive ethanol consumption. Alcohol consumption represents a health risk and it has been linked to unemployment. The aim of this study how working status predict alcohol consumption through a cross sectional study comparing alcohol-related biomarkers levels in office workers and unemployed people. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Local data pertaining to unemployment in this population are lacking. Previous studies [ 20 , 21 ] have shown that problem drinking is associated with losing a job and remaining unemployed. This finding suggests that they had lower socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Local data pertaining to unemployment in this population are lacking. Previous studies [ 20 , 21 ] have shown that problem drinking is associated with losing a job and remaining unemployed. This finding suggests that they had lower socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment has a significant contribution to drinking behavior ( 48 ), and this contribution is outstanding in the case of long-term unemployment ( 49 ). Unemployed people are also more likely to suffer from alcohol than workers ( 50 ). Therefore, alcohol consumption plays an intermediary role in the relationship between unemployment and economic growth, which is also one of the sources of asymmetry between unemployment and economic growth.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The association of excessive alcohol consumption with medical problems is well known [1,2], and its societal impact is substantial [3,4]. The World Health Organization estimates that 3.3 million deaths worldwide each year can be attributed to alcohol consumption [1].…”
Section: Introductionmentioning
confidence: 99%